Voltage regulation of an asynchronous wind turbine using STATCOM and a control strategy based on a combination of single input fuzzy logic regulator and sliding mode controllers - Mohammed Mokhtari; Smail Zouggar; Nacer K. M’Sirdi; Mohamed Larbi Elhafyani (Institute of Advanced Engineering and Science, 2020)
In the literature, it is well known that reactive power management is the greatest challenge in wind turbine based on a three-phase self-excited induction generator. Any variation of wind speed or load causes a variation on the needed reactive power and thus a voltage fluctuation. Flexible AC transmission device such as STATCOM become then a necessity to prevent voltage instability and hence voltage collapse at the point of common coupling. This paper proposes so a new control strategy for voltage regulation of an asynchronous wind turbine based on a combination of a single input fuzzy logic regulator and a sliding mode controller. Compared to the classical control strategy with PI regulators, the performance of the proposed compensator has been significantly improved when it is controlled by the new approach and the system have shown more robustness and stability regarding external disturbances. The present document traits so the modelling of the power system, the simulation results and the controller’s scheme and design.